Introduction to the African economy - "Graft-Johnson, J.C.De" (Bombay, 1959)
I should like to thank the Delhi School of Economics for inviting me to deliver a series of four lectures which were to serve as An introduction to the African Economy. Delhi University decision to place this lectures at the disposal of a wider public gave rise to the publication of this book which I hope will stimulate further the growing interest in the African economy.
Keywords: Economics